2013
DOI: 10.5552/drind.2013.1248
|View full text |Cite
|
Sign up to set email alerts
|

Usporedba momenta loma kutnog spoja izvedenoga upotrebom različitih ljepila

Abstract: • The main goal of this research is to determine the most

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
3
1
1
Order By: Relevance
“…The results of corner window frame double tenon glue joint strength produced from combined poplar-beech veneer LVL, showed that fail- (Table 7). The torque reached in this experiment was 2 to 3 times higher than that was in similar experiment by Hrovatin et al (2013) for corner connection strength glued with different adhesives. In this research authors examined spruce elements 68 x 98mm and the corner joint was implemented by innovative ring type of connection (this ring type of connection was prizewinning in the International fair in Geneva and Nürnberg -patent No.…”
Section: Corner Window Frame Double Tenon Glue Joint Strengthcontrasting
confidence: 51%
See 1 more Smart Citation
“…The results of corner window frame double tenon glue joint strength produced from combined poplar-beech veneer LVL, showed that fail- (Table 7). The torque reached in this experiment was 2 to 3 times higher than that was in similar experiment by Hrovatin et al (2013) for corner connection strength glued with different adhesives. In this research authors examined spruce elements 68 x 98mm and the corner joint was implemented by innovative ring type of connection (this ring type of connection was prizewinning in the International fair in Geneva and Nürnberg -patent No.…”
Section: Corner Window Frame Double Tenon Glue Joint Strengthcontrasting
confidence: 51%
“…Резултати тестирања угаоне везе рама прозора израђеног од комбинованог буковог и тополовог LVL-а, показали су да је угаона веза попуштала при просечној сили лома од 7093 N, односно просечном моменту силе од 900 Nm (Табела 7). Ова вредност момента силе је 2 до 3 пута већа у односу на вредности које су добили Hrovatin et al (2013) за угаону везу рама прозора лепљену различитим лепковима. У том истраживању аутори су користили профиле смрче попречног пресека 68 x 98 mm, а угаони спој урађен је помоћу дрвеног прстена (спој који је добио златну медаљу на Међународном сајму иновација у Женеви и на Међународном сајму иновација у Nürnbergu -патент бр.…”
Section: квалитет угаоне везе за рам прозораunclassified
“…The bending-moment capacity is strongly affected by the length and width of the tenon, while the width has a slight lower influence (Kasal et pairing of open full-width mortise-and-tenon-joint elements on the strength of joints, and this type of joint was found to be the strongest at a tight fit of 0.1 mm. The mortise-and-tenon joint, in combination with PVAc, provided the best strength for all investigated wood species (Vassiliou et al, 2016;Bardak et al, 2017), while PU glue has appropriate strength in comparison with PVAc, and can completely fill and cover the gaps between the elements of a joint (Hrovatin et al, 2013). The suitable construction type of chairs, constructed with defined tenon dimensions, has been determined based on the required load-carrying capacity (Kiliç et al, 2018;Hitka et al, 2018;Ayrilmis et al, 2020).…”
Section: Introduction 1 Uvodmentioning
confidence: 99%
“…In an investigation of effect of wood species and adhesive type on the stiffness of rail to leg mortise and tenon furniture joints, the type of glue was not important for spruce joints, whereas for beech, the stiffness of joints glued with PVAc was significantly higher than with PU adhesive (Záborský et al 2017). In comparison with PVAc, PU glue has appropriate strength, and, as they slightly expand during the hardening phase, can completely fill and cover the gaps between elements of joint (Hrovatin et al 2013). Dowel joints glued with PU adhesive showed improved mechanical properties in humid environments (Máchová et al 2019).…”
Section: Introductionmentioning
confidence: 99%